Selected readings in economics - Harvard University (Harvard, 1960)
The last two decades have witnessed the appearance of a notable volume of scholarly publications in English on the Soviet economy. This literature includes among other things many writings of an essay sort that have appeared in very diverse and sometimes not very acces sible sources. The purpose of this handbook is to make available in convenient form some of the more significant of the latter writings. The essays selected are not intended to constitute a systematic survey of the Soviet Economy but taken together with available monograph literature they may serve as an introduction to two major and related, but still distinct, themes: the organization and working principles of Soviet economic planning, and the process of Soviet economic growth. Among the writings considered, those bearing especially on the first theme have been grouped in Part I of this volume. Others, which bear especially on the second, appear in Part II.
Keywords: Economics